Social Partnership in Human Resources Management - BAREEVA, Irkyam Adgamovna; VASIN, Sergey Mikhailovich; SUGROBOVA, Galina Alekseevna; KORCHAGINA, Lunika Nikolaevna (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017DO - 10.14505/jarle.v8.8(30).04, 2018)
The present article provides a retrospective analysis of the views of various authors on the problem of social partnership, considering social partnership as an alternative to social confrontation, as a means to harmonize the interests of various social groups in the process of resolving emerging contradictions in various areas of public practice. It was pointed out that partnership allows striking a balance of mutual interests in achieving an overall objective, effectively allocating the available resources and opportunities. The article presents the analysis of the activities of a trade union organization as a social partner, the analysis of social and labor relations in an industrial business. The authors have revealed significant problems in the field of social partnership, on which they have developed several practical recommendations.The analysis is based on social activity index calculation in a trade union organization. To comply with confidentiality requirements, property rights and trade secrets, the enterprise name is not listed.